IOT Based Health Care System - D, Kumar; S, Ramkumar; R, Rubini (International Research Journal of Multidisciplinary Technovation, 2019)
The aim of this paper is to design an IOT based architecture for health related issues such as Diabetics, Heart Monitoring system, to check body temperature, Pulse rate and kidney functioning. we are analyzing different methods and techniques used for healthcare monitoring system where doctor can continuously monitor the patient's condition. The Data obtained through sensors are uploaded to the Ethernet module which is an IOT connected device to cloud and collected data is accessed by Authorized person through internet. Also the patient history will be stored in the web server and doctor can access the information whenever needed from any corner of the world. If there is any sudden change in the health condition of the person who are using this health care system module, automatically the data of the patient will be uploaded to the concerned doctor, within few minutes user will get a prescription for his current situation. This will connect us with the doctors who are very far from us, and the immediate action will increase the health rate of people. This health care system will be most useful in rural and remote areas.